The effect of hydrogel extract of kampung chicken feet (gallus domesticus) on the number of fibroblast cells in the wound healing process after tooth extraction in male wistar white rats (Rattus Norvegicus): Study experimental - Putra, Andrika Fitriyan; Edrizal, Edrizal (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Wound healing after tooth extraction is a complex process involving several phases, including proliferation, where fibroblasts play a vital role in tissue regeneration. Chicken feet hydrogel extract (Gallus domesticus) is rich in collagen, amino acids, omega-3, and calcium, which have the potential to enhance fibroblast numbers and accelerate wound healing.  This study aimed to analysis the effect of chicken feet hydrogel extract on the number of fibroblasts during the wound healing process following tooth extraction in male Wistar rats (Rattus norvegicus). Methods: This experimental study used a true experimental design with a positive control group (Povidone Iodine), a negative control group, and three treatment groups with hydrogel extract concentrations of 5%, 10%, and 15%. Observations were conducted on days 3, 7, and 14 to calculate the number of fibroblasts using histopathological techniques. The data obtained from the observation results were tested for normality. The normality test used was the Shapiro-Wilk test because the data was less than 50 and the results were as follows: The conclusion of the Shapiro-Wilk test is that the data is generally normal. Next, the Levene test was performed. Next, an ANOVA test was performed because the data requirements are normally distributed and homogeneous. Next, the LSD test was performed. Results: A significant increase in fibroblast numbers was observed in the treatment groups compared to the negative control group. The 15% concentration demonstrated the highest effectiveness in increasing fibroblast numbers on day 7. A decrease in fibroblast numbers was noted on day 14, coinciding with the tissue remodeling phase. Conclusion: Chicken feet hydrogel extract significantly enhances fibroblast numbers during the wound healing process after tooth extraction, particularly at a 15% concentration. These results indicate the potential of this extract as a natural alternative to accelerate wound healing.KEY WORDS: Hydrogel Extract, Chicken Feet, Fibroblasts, Wound Healing, Tooth ExtractionPerbedaan efek ekstrak hydrogel ceker ayam kampung (gallus domesticus) terhadap jumlah sel fibroblas pada proses penyembuhan luka pasca ekstraksi gigi pada tikus putih wistar jantan (rattus norvegicus): Studi eksperimentalABSTRAKPendahuluan: Penyembuhan luka pasca ekstraksi gigi merupakan proses kompleks yang melibatkan berbagai fase, termasuk proliferasi, di mana fibroblas memainkan peran penting dalam regenerasi jaringan. Ekstrak hydrogel ceker ayam kampung (Gallus domesticus) kaya akan kolagen, asam amino, omega-3, dan kalsium, yang berpotensi meningkatkan jumlah sel fibroblas dan mempercepat penyembuhan luka. Tujuan Penelitian ini bertujuan untuk menganalisis perbedaan efek ekstrak hydrogel ceker ayam kampung terhadap jumlah sel fibroblas pada proses penyembuhan luka pasca ekstraksi gigi pada tikus putih wistar jantan (Rattus norvegicus). Metode: Penelitian ini menggunakan desain eksperimental dengan kelompok kontrol positif (Povidone Iodine), kontrol negatif, dan tiga kelompok perlakuan dengan konsentrasi ekstrak hydrogel ceker ayam kampung 5%, 10%, dan 15%. Observasi dilakukan pada hari ke-3, 7, dan 14 untuk menghitung jumlah sel fibroblas menggunakan teknik histopatologi. Data yang didapatkan pada hasil pengamatan dilakukan Uji Normalitas. Uji normalitas yang digunakan adalah Shapiro-Wilk karena data kurang dari 50 diperoleh hasilnya sebagai berikut: Kesimpulan pada uji Shapiro-Wilk adalah secara keseluruhan data terbukti normal. Selanjutnya dilakukan uji Levene Test.  Selanjutnya dilakukan pengujian ANOVA karena syarat data berdistribusi normal dan homogen. Selanjutnya dilakukan uji LSD. Hasil: Terdapat peningkatan jumlah sel fibroblas yang signifikan pada kelompok perlakuan dibandingkan kontrol negatif. Konsentrasi 15% menunjukkan efektivitas tertinggi dalam meningkatkan jumlah fibroblas pada hari ke-7. Penurunan jumlah fibroblas diamati pada hari ke-14, seiring dengan fase remodeling jaringan. Simpulan: Ekstrak hydrogel ceker ayam kampung secara signifikan meningkatkan jumlah sel fibroblas pada proses penyembuhan luka pasca ekstraksi gigi, terutama pada konsentrasi 15%.KATA KUNCI: Ekstrak hydrogel ceker ayam kampung, Fibroblas, Penyembuhan luka, Ekstraksi gigi